ANALYSIS OF THEORETICAL VIEWS ON THE ACTIVITY OF MANAGEMENT BOARDS IN HIGHER EDUCATION INSTITUTIONS ON THE EXAMPLE OF THE EXPERIENCE OF FOREIGN COUNTRIES (Proceedings of International Educators Conference, 2024)
Governing boards play a critical role in shaping the strategic direction and governance of higher education institutions around the world. The activities and decisions of these boards have a significant impact on the academic, financial and administrative aspects of universities. In higher education institutions, governing boards set policy, oversee financial management, appoint key personnel and ensure compliance with regulations is responsible for They serve as the governing body that guides the institution toward its mission and goals. The composition of governing boards varies across countries, with some having a more centralized structure and others adopting a decentralized approach. Different theoretical perspectives shed light on the functioning and effectiveness of governing boards in higher education. Agency theory emphasizes the principal-agent relationship between the board of directors and university management, focusing on issues of accountability and alignment of interests. Resource dependence theory emphasizes the external dependence of universities and the role of governing boards in managing these relationships. Examining the experience of governing boards in foreign countries provides valuable insights into best practices and challenges. For example, countries such as the United States have a strong tradition of shared governance in which faculty members play an important role in decision-making processes. In contrast, some European countries have more centralized governance structures with a focus on efficiency and accountability.[1]